Muhammadiyah's Untold Story; A Welfare State Vision Through Higher Education System - Sholahuddin Al-Fatih (Jurnal Muhammadiyah Studies, 2024)
This research discusses Muhammadiyah's strategic role in building a vision of a welfare state through the higher education system it has developed. As one of the largest Islamic organizations in Indonesia, Muhammadiyah not only focuses on religious aspects but also makes significant contributions in the social, economic, and educational fields. This article explores the rarely revealed history regarding Muhammadiyah's mission and vision in creating a prosperous society. An innovative higher education system approach is used as the main tool for producing superior human resources that support the achievement of national prosperity goals. By using qualitative methods through document analysis and in-depth interviews, this research found that Muhammadiyah's higher education model integrates Islamic values ​​with the demands of modernity, thereby producing graduates who are competent and have character. It is hoped that the results of this research will provide a new understanding of the role of higher education in realizing a vision of inclusive and sustainable prosperity in Indonesia.